Utilisation of a community-based health facility in a low-income urban community in Ibadan, Nigeria - Ayodeji M. Adebayo; Michael C. Asuzu (AOSIS, 2015)
Background: Primary healthcare is established to ensure that people have access to health services through facilities located in their community. However, utilisation of health facilities in Nigeria remains low in many communities. Aim: To assess the utilisation of community-based health facility (CBHF) amongst adults in Ibadan, Nigeria. Settings: A low-income community in Ibadan North West Local Government Area of Oyo State.Methods:A cross-sectional survey was conducted using a simple random sampling technique to select one adult per household in all 586 houses in the community. A semi-structured interviewer-administered questionnaire was used to collect information on respondents' sociodemographic characteristics, knowledge and utilisation of the CBHF. Data analysis included descriptive statistics and association testing using the Chi-square test at p = 0.05. Results: The mean age of the respondents was 46.5 ± 16.0 years; 46.0% were men and 81.0% married; 26% had no formal education and 38.0% had secondary-level education and above; traders constituted 52.0% of the sample; and 85.2% were of low socioeconomic standing; 90%had patronised the CBHF. The main reasons for non-utilisation were preference for general hospitals (13.8%) and self-medication (12.1%). Respondents who had secondary education and above, were in a higher socioeconomic class, who had good knowledge of the facility and were satisfied with care, utilised the CBHF three months significantly more than their counterparts prior to the study (p < 0.05). However, only satisfaction with care was found to be a significant predictor of utilisation of the CBHF. Conclusion: The utilisation of the CBHF amongst adults in the study setting is high, driven mostly by satisfaction with the care received previously. Self-medication, promoted by uncontrolled access to drugs through pharmacies and patent medicine stores, threatens this high utilisation.